2011
DOI: 10.1016/j.pain.2011.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Motor cortex stimulation reduces hyperalgesia in an animal model of central pain

Abstract: Electrical stimulation of the primary motor cortex has been used since 1991 to treat chronic neuropathic pain. Since its inception, motor cortex stimulation (MCS) treatment has had varied clinical outcomes. Until this point, there has not been a systematic study of the stimulation parameters that most effectively treat chronic pain, or of the mechanisms by which MCS relieves pain. Here, using a rodent model of central pain, we perform a systematic study of stimulation parameters used for MCS and investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 65 publications
(86 reference statements)
7
79
1
3
Order By: Relevance
“…GABAergic transmission in the ZI is complex. Cha et al reported that muscimol injection into the ZI evoked ZI neuron inactivation,52,53 but the results of Moon et al did not agree 13. It would be possible to target on complex ZI itself and posterior thalmaus.…”
Section: Discussionmentioning
confidence: 98%
“…GABAergic transmission in the ZI is complex. Cha et al reported that muscimol injection into the ZI evoked ZI neuron inactivation,52,53 but the results of Moon et al did not agree 13. It would be possible to target on complex ZI itself and posterior thalmaus.…”
Section: Discussionmentioning
confidence: 98%
“…The only plausible explanation that has been suggested for the effect of MCS is that it acts as a descending modulator. 12,27 More studies are required to understand the relationship between MCS and neuropathic pain. We hypothesized that MCS acts as not only a descending modulator but also an ascending modulator of pain pathways.…”
Section: Fig 5 Comparison Of the Behavioral Test Results Between Ipmentioning
confidence: 99%
“…Fonoff et al 12 and Lucas et al 27 hypothesized that MCS stimulates serotonin secretion in the periaqueductal gray (PAG) directly, or indirectly via the zona incerta (ZI). Therefore, we expected to observe changes in serotonin levels in the spinal cord.…”
Section: How Does Mcs Affect the Descending Pathway?mentioning
confidence: 99%
“…Bachmann et al, 2013). Intriguingly, the motor and sensory aspects of cortical reorganization after spinal cord injury seems to be tightly linked, as suggested by the beneficial effects induced by motor cortex stimulation on central pain (Lucas et al, 2011, Cha et al, 2013; Jiang et al, 2013). …”
Section: Cortical Reorganization Depends On Species (Fig 1)mentioning
confidence: 99%